Scaling the nexus: Towards integrated frameworks for analysing water, energy and food. Issue 4 (30th May 2018) - McGrane, Scott J.; Acuto, Michele; Artioli, Francesca; Chen, Po‐Yu; Comber, Robert; Cottee, Julian; Farr‐Wharton, Geremy; Green, Nicola; Helfgott, Ariella; Larcom, Shaun; McCann, Julie A.; O'Reilly, Patrick; et al.
Abstract : The emergence of the water–energy–food (WEF) nexus has resulted in changes to the way we perceive our natural resources. Stressors such as climate change and population growth have highlighted the fragility of our WEF systems, necessitating integrated solutions across multiple scales. While a number of frameworks and analytical tools have been developed since 2011, a comprehensive WEF nexus tool remains elusive, hindered in part by our limited data and understanding of the interdependencies and connections across the WEF systems. To achieve this, the community of academics, practitioners and policy‐makers invested in WEF nexus research are addressing several critical areas that currently remain as barriers. First, the plurality of scales (e.g., spatial, temporal, institutional, jurisdictional) necessitates a more comprehensive effort to assess interdependencies between water, energy and food, from household to institutional and national levels. Second, and closely related to scale, a lack of available data often hinders our ability to quantify physical stocks and flows of resources. Overcoming these barriers necessitates engaging multiple stakeholders, and using experiences and local insights to better understand nexus dynamics in particular locations or scenarios, and we exemplify this with the inclusion of a UK‐based case study on exploring the nexus in a particular geographical area. We elucidate many challenges that have arisen across nexus research, including the impact of multiple scales in operation, and concomitantly, what impact these scales have on data accessibility. We assess some of the critical frameworks and tools that are applied by nexus researchers and articulate some of the steps required to develop from nexus thinking to an operationalisable concept, with a consistent focus on scale and data availability. Abstract : The water‐energy‐food (WEF) nexus has emerged, and resulted in, significant changes to the way we perceive the interdependencies and feedbacks across the three sectors. Here, we address the data issues that are central to mapping these interdependencies, and provide an assessment of the existing frameworks that are utilised within WEF nexus research.